Cognitive dissonance of online socialization among tertiary students - Johari, Aiza; Sarkawi, Adib; Awang Shuib, Awang Rozaimie; Bujang, Azlina; Bibi, Zainon (2016)
Social networking sites (SNS) are designed to ease online information sharing and enhance information sharing among people, and the sites also relate to socio-cultural, academic, entertainment, educational and business domains. From teaching and learning perspectives, SNS increase comprehension effectiveness and allow faster information accesses.Today, tertiary students’ lives are synonymous with network connectivity. This paper argues that socializing online could affect interpersonal relationship among them. A sufficient cognitive dissonance is required to prevent cyberspace addiction.Hence, the study investigates the extent of SNS that affects academic enhancement among the undergraduates. Their levels of awareness on the potential risks of social networking are also identified.The finding revealed that majority of the respondents found that social networking sites are necessary (especially Facebook).They spent more than half of their daily routine being online.Most of the respondents were also aware of potential risks of SNS.Therefore, self-discipline and self-awareness regarding the risks of social networking sites are crucial to enhance their potential values.